A Textual Interpretation of Mandailing Oral Tradition: A Cultural Maintenance Model - Mara Untung Ritonga (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
Language has the pivot on which the culture grow or turn to extinct. Language is as primary means of cultural events transmission. A digitalised adage as one of efforts to revitalise or maintain the culture will not be received without understanding the meanings of the oral tradition texts as their implicitness. This research tries to fill the space left by other researchers to make young generation of Mandailing understand the meanings of the oral tradition texts. The oral tradition tells a great deal of local genuine. By doing so, it is expected the young generation can pick out the beneficial messages from the oral tradition texts, then, to guide them in the action, behaviour, and thinking. Therefore, the oral traditonal needs to maintain or to reserve. With respect to the nature, the out put of this research is to design a maintenance model of Mandailing oral tradition. The subject of the research is the oral tradition of Mandailing analisyed through cognitive semantics, and CDA as theoretical tools for textual interpretation. The qualitative and quantitative data of the research show  that the oral traditon of Mandailing; mangandung and marturi include in the category of extinct, while mangambat, mangalehenmangan, manjair, maralok-alok, mambue, marturas, maronang-onang, marsilogo, marungut-ungut, and marpege-pege are in the category of endangered traditon. The cultural activities of the oral traditon do not transmit towards the young generation of Mandailing (age. 17- 40) taken from 100 respondent. Theydid not understand the meaning of the oral traditon texts (87%). The other factor is very few young generation  (10%) involve in the cultural traditon of the oral tradition.